ROBOT-ASSISTED SURGERY IN PAKISTAN: A SWOT ANALYSIS - MUJAHID , MUF; BAIG , Z (Biological and Clinical Sciences Research Journal, 2023)
The Sindh Government Qatar Hospital in Karachi installed Pakistan’s first DaVinci S (DVS) system in 2011. Later, in 2013, Civil Hospital Karachi adopted more advanced DaVinci Si (DVSi) robotic equipment. Recently, in April 2023, the Pakistan Kidney and Liver Institute (PKLI) performed Radical Nephrectomy Robot-assisted Surgery. Essential search terms were finalized for a systematic review, and selection criteria were defined. The finalized keywords were entered into Pub-Med, Pakmedinet, and ERIC databases, resulting in 2084 articles. Grey literature was searched through Google Scholar, yielding 509 articles. After the initial screening of 437 out of 509 studies, 72 articles met the eligibility requirements according to the PRISMA guidelines. However, 39 articles were excluded, leaving 33 to be incorporated into the study. A successful robotic surgery program requires well-trained operating room personnel, dedicated surgeons, supportive hospital administration, adequate financial resources, and a strong marketing strategy. Despite meta-analyses indicating that robotic surgery has not outperformed conventional surgery, marketing can help mitigate the high treatment costs by increasing the number of patients, thereby ensuring the program’s long-term viability.